Spectrophotometric Determination of pKa and Log P of Risperidone - Sunil Kumar Dubey,Gautam Singhvi,Abhay Tyagi,Himanshu Agarwal,K. V. Krishna (Journal of Applied Pharmaceutical Science, 2017)
Objective: Determination of pKa and Log P of Risperidone by spectrophotometric technique. Materials and Methods: From the perspective of dosage form design and pharmaceutical analysis, the dissociation constant and partition coefficient are the most important physicochemical properties of a drug which need to be determined. The pKa determination of Risperidone was carried out using a simple UV–Visible spectrophotometric method and Log P was estimated using shake flask method followed by UV analysis. Results and Conclusion: Experimental value of pKa and log P for Risperidone, an anti-psychotic drug, has been reported for the first time. The pKa value of Risperidone was found to be 8.62 and log P of Risperidone was estimated to be 3.50.
Keywords: Anti-psychotic,Dissociation constant,Partition coefficient,Validation.